2020
DOI: 10.4084/mjhid.2020.046
|View full text |Cite
|
Sign up to set email alerts
|

A A Multicentre ICET-A Study of Confirmed SARS-CoV-2 Infection in Patients with Hemoglobinopathies: Preliminary Data from 10 Countries

Abstract: Objectives: This study aims to investigate, retrospectively, the epidemiological and clinical characteristics, laboratory results, radiologic findings and outcomes of novel coronavirus disease-19 (COVID-19) in patients with transfusion dependent β thalassemia (β-thalassemia major-TM), non-transfusion dependent β thalassemia (β-thalassemia intermedia -TI) and sickle cell disease (SCD). Design, setting: A total of 17 Centers, from 10 countries, following 9,499 patients with hemoglobinopathies participated in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This finding is comparable to several previous studies from different populations. 22 24 Additionally, ESR was significantly higher in the symptomatic compared to asymptomatic patients. The ESR level reportedly is positively associated with the severity of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 92%
“…This finding is comparable to several previous studies from different populations. 22 24 Additionally, ESR was significantly higher in the symptomatic compared to asymptomatic patients. The ESR level reportedly is positively associated with the severity of COVID-19 infection.…”
Section: Discussionmentioning
confidence: 92%
“…A multicenter study by de Sanctis et. al 28 and another study by Panepinto et al 29 established increased female prevalence (76.9% and 57% respectively) of COVID-19 infection among patients with hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 91%
“…A multicenter study by de Sanctis et. al28 and another study by Panepinto et al29 established increased female prevalence (76.9% and 57% respectively) of COVID-19 infection among patients with hemoglobinopathies. Among the comorbidities evaluated in all patients with COVID-19, resultsdemonstrated that almost half of those with SCD were found to have G6PD deficiency in contrast to a minority in the control group.…”
mentioning
confidence: 91%
“…Obesity, cardiovascular disease, hemoglobinopathies, cancer, and diabetes mellitus are risk factors for COVID-19 severity. 3 5 Furthermore, in one cohort study, a blood-group–specific analysis demonstrated a higher risk in blood group A than in other blood groups and a protective effect in blood group O compared with other blood groups. 6 …”
mentioning
confidence: 99%
“…Moreover, close monitoring of pulmonary artery pressure measurement to detect pulmonary artery hypertension timely is essential to reduce the potential COVID-19 severity in patients with NTDT. 3 , 13 Furthermore, thrombo-inflammatory abnormalities are implicated in the progression of COVID-19, and thalassemia patients are already prone to thrombotic events, mostly in NTDT patients 8 requiring an appropriate treatment to prevent the risks of COVID-19. Finally, our data showed that the comorbidities associated with the severity of COVID-19 in thalassemia patients were not different from the general infected population.…”
mentioning
confidence: 99%